How well are Brazilian mastologists (breast surgeons) trained in breast reconstruction and oncoplastic surgery? A study of the impact of a breast reconstruction and oncoplastic surgery improvement course - Businaro Fernandes João, Thais; de Oliveira, Vilmar Marques; Bagnoli, Fábio; Bastos, Maria Carolina Soliani; Rinaldi, José Francisco; Brenelli, Fabrício Palermo; Mateus, Evandro Fallaci (Frontiers in Oncology, 2023)
Introduction: In 2002, Veronesi and Fisher established conservative surgery for breast cancer. The breasts are a female symbol, impacts self-image and self-esteem. Breast reconstructive and oncoplastic surgeries have an important role in minimizing injuries. In Brazil less than a third of public health system (SUS) users have access to immediate reconstructive surgery. The low rate of breast reconstructions has multiple causes and the deficiency in availability and surgeons’ technical qualification play a role. In 2010, the Breast Reconstruction and Oncoplastic Surgery Improvement Course was created by professors of the Mastology Department of Santa Casa de São Paulo. The objectives of this study were to evaluate the impact of the techniques learned on patients’ management by the surgeons enrolled in the Course, as well as to characterize their profile. Methods: All students enrolled in the Improvement Course between 2010 and 2018 were invited to answer an online questionnaire. Students who did not agree to answer the questionnaire or answered them incompletely were excluded. Results: Total students included: 59. The mean age: 48.9 years, male (72%) with more than 5 years of Mastology practice (82.2%), from all regions of Brazil, 1.7% from the North, 33.9% from the Northeast, 44.1% from the Southeast, and 12% from the South. Most of the students considered they had little or no knowledge of breast reconstruction (74.6%) and 91,5% did not consider they had enough aptitude to perform breast reconstructions after finishing residency. After the Course, 96.6% considered themselves apt to perform such surgeries. Over 90% of the students considered the Course had impacted their practice and changed their surgical strategy view. Before the Course, 84.8% of the students stated that less than half of their patients who were operated on for breast cancer had breast reconstruction, compared to 30.5% after the Course. Conclusion: The Breast Reconstruction and Oncoplastic Surgery Improvement Course studied here positively impacted the Mastology surgeons' management of patients. They stated they learned the surgical techniques and felt confident to implement them in their practice, leading to an expressive increase in the number of breast reconstructive surgeries performed in their workplaces in Brazil.